Pathophysiology and Treatment of Alien Hand Syndrome. (5th December 2014) - Sarva, Harini; Deik, Andres; Severt, William Lawrence
Background: Alien hand syndrome (AHS) is a disorder of involuntary, yet purposeful, hand movements that may be accompanied by agnosia, aphasia, weakness, or sensory loss. We herein review the most reported cases, current understanding of the pathophysiology, and treatments. Methods: We performed a PubMed search in July of 2014 using the phrases "alien hand syndrome, " "alien hand syndrome pathophysiology, " "alien hand syndrome treatment, " and "anarchic hand syndrome." The search yielded 141 papers (reviews, case reports, case series, and clinical studies), of which we reviewed 109. Non-English reports without English abstracts were excluded. Results: Accumulating evidence indicates that there are three AHS variants: frontal, callosal, and posterior. Patients may demonstrate symptoms of multiple types; there is a lack of correlation between phenomenology and neuroimaging findings. Most pathologic and functional imaging studies suggest network disruption causing loss of inhibition as the likely cause. Successful interventions include botulinum toxin injections, clonazepam, visuospatial coaching techniques, distracting the affected hand, and cognitive behavioral therapy. Discussion: The available literature suggests that overlap between AHS subtypes is common. The evidence for effective treatments remains anecdotal, and, given the rarity of AHS, the possibility of performing randomized, placebo-controlled trials seems unlikely. As with many other interventions for movement disorders, identifying the specific functional impairments caused by AHS may provide the best guidance towards individualized supportive care.